Protein assemblies ejected directly from native membranes yield complexes for mass spectrometry - Chorev, D; Baker, L; Wu, D; Beilsten-Edmands, V; Rouse, S; Zeev-Ben-Mordehai, T; Jiko, C; Samsudin, F; Gerle, C; Khalid, S; Stewart, A; Matthews, S; et al. (American Association for the Advancement of Science, 2018)
Membrane proteins reside in lipid bilayers and are typically extracted from this environment for study, which often compromises their integrity. In this work, we ejected intact assemblies from membranes, without chemical disruption, and used mass spectrometry to define their composition. From Escherichia coli outer membranes, we identified a chaperone-porin association and lipid interactions in the β-barrel assembly machinery. We observed efflux pumps bridging inner and outer membranes, and from inner membranes we identified a pentameric pore of TonB, as well as the protein-conducting channel SecYEG in association with F1FO adenosine triphosphate (ATP) synthase. Intact mitochondrial membranes from Bos taurus yielded respiratory complexes and fatty acid–bound dimers of the ADP (adenosine diphosphate)/ATP translocase (ANT-1). These results highlight the importance of native membrane environments for retaining small-molecule binding, subunit interactions, and associated chaperones of the membrane proteome.